Reduction of Computed Tomography Use for Pediatric Closed Head Injury Evaluation at a Nonpediatric Community Emergency Department. (1st February 2019) - Puffenbarger, Melissa S.; Ahmad, Fahd A.; Argent, Michelle; Gu, Hongjie; Samson, Charles; Quayle, Kimberly S.; Saito, Jacqueline M.
Abstract: Objective: The purpose of this study was to determine if implementation of a Pediatric Emergency Care Applied Research Network (PECARN)‐based Closed Head Injury Assessment Tool could safely decrease computed tomography (CT) use for pediatric head injury evaluation at a nonpediatric community emergency department (ED). Methods: A quality improvement project was initiated at a nonpediatric community ED to implement an institution‐specific, PECARN‐based Pediatric Closed Head Injury Assessment Tool. Baseline head CT use at the participating ED was determined for children with closed head injury through retrospective chart review from March 2014 through November 2015. Head injury patients were identified using International Classification of Disease (ICD)‐9 codes for head injury, unspecified (959.01) and concussion with and without loss of consciousness (850–850.9) until October 2015, after which ICD‐9 was no longer used. To identify eligible patients after October 2015, lists of all pediatric patients evaluated at the participating ED were reviewed, and patients were included in the analysis if they had a physician‐assigned discharge diagnosis of head injury or concussion. Exclusion criteria were age ≥ 18 years, penetrating head trauma, history of brain tumor, ventriculoperitoneal shunt, bleeding disorder, or presentation > 24 hours postinjury. Medical history, injury mechanism, symptoms, head CT use, and disposition were recorded. Implementation of the Pediatric Closed Head Injury Assessment Tool was achieved through provider education sessions beginning in December 2015 and ending in August 2016. Head CT use was monitored for 12 months postimplementation, from September 2016 through August 2017. Patients were classified into low, intermediate, or high risk for clinically important traumatic brain injury (ciTBI) by chart review. ED length of stay (LOS), disposition, and ED returns within 72 hours were recorded. Categorical variables were compared using chi‐square test or Fisher's exact test, and continuous variables, using Kruskal‐Wallis test. Results: A total of 252 children with closed head injury were evaluated preimplementation (March 2014 through November 2015), 132 children were evaluated during implementation (December 2015 through August 2016), and 172 children were evaluated postimplementation (September 2016 through August 2017). Overall CT use decreased from 37.7% (95% confidence interval [CI] = 31.7–43.7) preimplementation to 16.9% (95% CI = 11.3–22.5) postimplementation (p < 0.001). Only 1% (95% CI = 0%–2.9%) of low‐risk patients received a head CT postimplementation compared to 22.6% (95% CI = 16.1%–29.1%) preimplementation (p < 0.001). CT use among patients ≥ 24 months decreased from 42.9% (95% CI = 36.5%–49.6%) to 19.6% (95% CI = 13.1%–26.1%; p < 0.001) and remained low and unchanged for patients < 24 months. Transfers to a pediatric trauma center and ED returns within 72 hours were unchanged, while median ED LOS improved from 1.5 to 1.3 hours (p = 0.03). There were no missed ciTBIs after implementation of the guideline. Conclusion: Implementation of the PECARN‐based Pediatric Closed Head Injury Assessment Tool reduced head CT use in a nonpediatric ED. The greatest impact was seen among children aged ≥ 24 months at very low risk for ciTBI.